PENGARUH KETIDAKPASTIAN LINGKUNGAN YANG DIPERSEPSIKAN DAN STRATEGI KOMPETITIF TERHADAP HUBUNGAN SISTEM KONTROL AKUNTANSI DENGAN KINERJA PERUSAHAAN - Sabaruddinsah, Sabaruddinsah (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2010)
The main objective of the study is to examine the influence of perceived environment uncertainty and competitive strategy to ward the accounting control system and company performance. The sample of this study was selected by using multistaged sampling method. The questionaires has been distributed to the population target (about 186), namely top manager of pharmaceutical company in Indonesia dan only 67 questionaires had been returned. The estimation technique to prove the hypothesis is using residual analysis as outlined by Duncan and Moores (1989).The residual analysis has performed as a good approach to cope the problem of multicollinearity in stastical estimated.The results found that perceived environment uncertainty and competitive strategy were not positively influence to relationship of accounting control system and company performance. Finally, this study suggests that the decision maker of the certain company should rely on perceived environment uncertainty and competitive strategy in order to achieve a highly performance and good in control system.